Extremity Arterial Thromboses in Hospitalized Children: A National Database Analysis of Prevalence and Therapeutic Interventions. Issue 3 (March 2019) - Totapally, Balagangadhar R.; Raszynski, Andre; Khan, Danyal; Amjad, Ibrahim; Biehler, Jefry
Abstract : Objectives: The purpose of this study was to evaluate the prevalence, demographics, predisposing conditions, therapeutic interventions, and outcomes of extremity arterial thrombosis in hospitalized children. Design: Retrospective cohort study. Patients: National discharge database analysis. Measurements and Main Results: Cases of extremity arterial thrombosis in children and neonates were extracted from the Kids' Inpatient Database 2012. These were analyzed and compared with other discharges for prevalence, demographics, treatments, outcomes, and further analyzed by age group and select predisposing conditions. A total of 961 children with extremity arterial thrombosis (prevalence of 2.35/10, 000 discharges) were included in our analysis. The median age of extremity arterial thrombosis patients was significantly lower when compared with other pediatric discharges (1 yr [interquartile range, 0–15 yr) vs 3 yr [interquartile range, 0–16 yr]; p < 0.0001). The proportion of females with extremity arterial thrombosis was lower (41.4% vs 53.3%; odds ratio, 0.62; 95% CI, 0.55–0.70) with no racial/ethnic variation in the prevalence of extremity arterial thrombosis. An upper extremity was involved in 18.1% and a lower extremity in 83.3%. Arterial cannulation and cardiac catheterization were much more common in the younger age groups. External trauma was documented in 13.2% of all patients with extremity arterial thrombosis and was more frequent in older age groups. A systemic thrombolytic medication was administered to 5.7% of the patients, thromboembolectomy was performed in 11.8% of the cases, and 3.1% of the patients required amputation. There was a significant variation in the use of thrombolysis, thrombectomy/embolectomy, or requirement for amputation limb based on age groups and underlying predisposing condition. Conclusions: The study describes the national prevalence of extremity arterial thrombosis in hospitalized children. The management strategies of extremity arterial thrombosis vary with age and underlying predisposing factors.